2008
DOI: 10.1021/jp802089r
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Free MALDI Investigation of the Cationization of Linear Polyethers with Alkali Metals

Abstract: The MALDI technique with solvent-free sample preparation has been applied to evaluate relative gas-phase affinities of polyether chain polymers with alkali metal cations. The study is performed on poly(ethylene glycol) and poly(propylene glycol) polymers of different lengths (PEG600, PEG1000, PPG425, PPG750) and the alkali metal cations Li(+), Na(+), K(+), and Cs(+). The experiments show that the lattice energy of the alkali metal salts employed as cation precursors can have a strong influence on the outcome o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 32 publications
4
35
0
Order By: Relevance
“…In these experiments, the difference in lattice energy of the alkali metal salts employed as cation precursors prevents the use of more than two cations in as ingle sample. [31,32] The solvent-free measurements corroborate the behavior found forc yclodextrins and polyethers in previous investigations; [31,32] in the absence of solvent, the stabilityo ft he complexes is highest for Li + ,a nd decreases rapidly with increasingc ation size. This is ac onsequence of the greater charge density of the smaller cations,w hich leads to at ighter coordination with the oxygen atoms of the host, involving shorter interaction distances.…”
Section: Experiments In Aqueousand Solvent-free Environmentssupporting
confidence: 86%
See 2 more Smart Citations
“…In these experiments, the difference in lattice energy of the alkali metal salts employed as cation precursors prevents the use of more than two cations in as ingle sample. [31,32] The solvent-free measurements corroborate the behavior found forc yclodextrins and polyethers in previous investigations; [31,32] in the absence of solvent, the stabilityo ft he complexes is highest for Li + ,a nd decreases rapidly with increasingc ation size. This is ac onsequence of the greater charge density of the smaller cations,w hich leads to at ighter coordination with the oxygen atoms of the host, involving shorter interaction distances.…”
Section: Experiments In Aqueousand Solvent-free Environmentssupporting
confidence: 86%
“…Previous studies have demonstrated that the stabilityo f these inclusion complexes in the gas phasei sm aximal for Li + and decreases rapidly with the size of the cation. [31,32] This was specifically shown for cyclodextrins in solvent-free laser desorptione xperiments in which,f or instance, a1 0-foldg reater abundance was found for the aCD-Li + complex relative to the aCD-K + complex. [31] Similar solvent-free measurements performed here for the CI calixarene corroboratet hose findings (see Section 2.2).…”
Section: Laser Desorption Experiments In Rtil Solutionsmentioning
confidence: 89%
See 1 more Smart Citation
“…In this study, the interaction energies for the 15-crown-5 complexes fall in this order: K + < Na [7][8]. Qualitatively it has also been observed in experiments for non-cyclic polyether's [19].…”
Section: Structure Of the [M(15-supporting
confidence: 78%
“…8 The advent of solvent-free sample preparation has made MALDI mass spectrometry (MALDI-MS) applicable to polyether chain polymers 9 or polymers that are insoluble in common organic solvents. [10][11][12][13] The solvent-free method is known to have several advantages, including investigations of the MALDI mechanism, 9,14 the possibility of multi-sample preparations, 15 analyses of insoluble synthetic polymers, 11 and the removal of potential solvent-induced chemical modifications.…”
Section: Introductionmentioning
confidence: 99%